Encyclopaedia of educational psychology, Vol.4 # Encyclopaedia of educational psychology Child psychology and education Vol.4 - Chawla, Ganesh Kumar; Chawla, Ganesh Kumar (New Delhi Arpan Publishing, 2013)
Introduction to child psychology